“SHOW ME AND I KNOW HOW TO WRITE!” UNIVERSITY STUDENT WRITERS’ VOICES DURING THESIS WRITING - Misdi, Misdi; Dwiniasih, Dwiniasih; Nasiba Zaripbayeva (Cirebon International Conference on Education and Economics Proceeding, 2024)
Critical writing in the contexts of academic writing is an interesting issue in the twenty-first century. In terms of thesis writing, student-writer and supervisor often come to a negotiation in order to gain high quality thesis. Of fifteen student-writers, two willingly joined and participated in the study. A good process of supervision conceptualizes on the students’ perception on their crucial periods of their study. Both research students and supervisors have to work effectively and efficiently in terms of the quality and quantity of the process of supervision. And it, therefore, is aimed to provide a phenomenon of how academic writing (thesis writing) needs to build student researchers’ autonomy.